2013
DOI: 10.1186/1471-2458-13-581
|View full text |Cite
|
Sign up to set email alerts
|

Rural-urban disparities in child nutrition in Bangladesh and Nepal

Abstract: BackgroundThe persistence of rural-urban disparities in child nutrition outcomes in developing countries alongside rapid urbanisation and increasing incidence of child malnutrition in urban areas raises an important health policy question - whether fundamentally different nutrition policies and interventions are required in rural and urban areas. Addressing this question requires an enhanced understanding of the main drivers of rural-urban disparities in child nutrition outcomes especially for the vulnerable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
76
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 35 publications
18
76
2
7
Order By: Relevance
“…Although many of the previous studies identified that rural children are more vulnerable to be malnourished [32][33][34], this study found that children living in urban area are more vulnerable to be stunted in Bangladesh. The urban population in last few decades has changed a lot due to migration of rural people to urban area for work and other opportunities.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Although many of the previous studies identified that rural children are more vulnerable to be malnourished [32][33][34], this study found that children living in urban area are more vulnerable to be stunted in Bangladesh. The urban population in last few decades has changed a lot due to migration of rural people to urban area for work and other opportunities.…”
Section: Discussioncontrasting
confidence: 68%
“…In developing countries, the rural-urban disparities in child nutrition outcomes remained persistent since long [32][33][34] presumably due to the difference in economic levels and poor accessibility to health facilities, education and other factors. Although many of the previous studies identified that rural children are more vulnerable to be malnourished [32][33][34], this study found that children living in urban area are more vulnerable to be stunted in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Significant relationships between wealth and stunting have been reported in numerous studies (e.g. Hong and Mishra, 2006;Johnson and Brown, 2014;Srinivasan et al, 2013). Wealthier households are likely to have greater access to food or may be less reliant on rice alone.…”
Section: Stunting and Ndvimentioning
confidence: 93%
“…20 Beberapa penelitian menyatakan bahwa sebagian besar balita malnutrisi tidak mendapatkan ASI eksklusif. 10,21 Angka cakupan ASI eksklusif terus mengalami penurunan dan pemberian susu formula pada bayi semakin meningkat meskipun para tenaga kesehatan telah bekerja sama untuk meningkatkan pemberian ASI eksklusif. 22 Hal ini yang merupakan salah satu faktor pemicu kejadian malnutrisi pada balita.…”
Section: Pembahasanunclassified
“…7,8,9 Penelitian yang dilakukan pada balita malnutrisi di Bangladesh dan Nepal menyatakan terdapat perbedaan karakteristik antara responden perkotaan dan pedesaan yaitu perbedaan dalam skor-z, jenis kelamin, vaksinasi pada anak, pendidikan orang tua, tingkat kesejahteraan, rasio ketergantungan dan jumlah anak yang berusia kurang dari lima tahun. 10 Faktor-faktor lain selain faktor kesehatan, tetapi juga merupakan masalah utama gizi buruk adalah stigma masyarakat, sosial budaya, kemiskinan, pendidikan rendah, ketersediaan pangan dan kesempatan kerja sebagai dampak urbanisasi. 11,12 Penelitian ini bertujuan untuk mengidentifikasi kejadian malnutrisi akut berat dan determinannya pada balita di wilayah perkotaan dan perdesaan di Yogyakarta.…”
unclassified